High glucose concentrations mask cellular phenotypes in a stem cell model of tuberous sclerosis complex - Rocktäschel, P; Sen, A; Cader, MZ (Elsevier, 2019)
Tuberous sclerosis complex (TSC) is a neurodevelopmental disorder caused by deletions in the TSC1 or TSC2 genes that is associated with epilepsy in up to 90% of patients. Seizures are suggested to start in benign brain tumors, cortical tubers, or in the perituberal tissue making these tubers an interesting target for further research into mechanisms underlying epileptogenesis in TSC. Animal models of TSC insufficiently capture the neurodevelopmental biology of cortical tubers, and hence, human stem cell-based in vitro models of TSC are being increasingly explored in attempts to recapitulate tuber development and epileptogenesis in TSC. However, in vitro culture conditions for stem cell-derived neurons do not necessarily mimic physiological conditions. For example, very high glucose concentrations of up to 25 mM are common in culture media formulations. As TSC is potentially caused by a disruption of the mechanistic target of rapamycin (mTOR) pathway, a main integrator of metabolic information and intracellular signaling, we aimed to examine the impact of different glucose concentrations in the culture media on cellular phenotypes implicated in tuber characteristics. Here, we present preliminary data from a pilot study exploring cortical neuronal differentiation on human embryonic stem cells (hES) harboring a TSC2 knockout mutation (TSC2 −/−) and an isogenic control line (TSC2 +/+). We show that the commonly used high glucose media profoundly mask cellular phenotypes in TSC2 −/− cultures during neuronal differentiation. These phenotypes only become apparent when differentiating TSC2 +/+ and TSC2 −/− cultures in more physiologically relevant conditions of 5 mM glucose suggesting that the careful consideration of culture conditions is vital to ensuring biological relevance and translatability of stem cell models for neurological disorders such as TSC.